The Role of Educated Women in Family Dynamics and Children's Early Childhood Education in Oyi Local Government Area, Anambra State, Nigeria - Ngozi Ugobueze, Ann (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study explores the role of educated women in shaping family dynamics and enhancing children's early childhood education in Oyi Local Government Area, Anambra State, Nigeria. The study utilized a survey research design to evaluate the impact of women's education on the socio-economic status of families in Oyi Local Government Area, Anambra State. Covering five townsÔÇöAwkuzu, Nteje, Umunnya, Ogbunike, and NkwelleÔÇöthe research targeted diverse women, including literates and illiterates from varied occupations. A sample of 200 working-class women was randomly selected from schools, banks, markets, and farms, with each town contributing 40 respondents. Data was collected via a questionnaire using a four-point Likert scale. The findings reveal that educated women contribute significantly to the economic stability of their families, engaging in diverse financial responsibilities, including healthcare, education, and property investments. They also demonstrate a preference for smaller, well-managed families, effectively using reproductive health information to maintain family planning. In the context of early childhood education, educated women actively support their children's learning through guidance on schoolwork, provision of educational materials, and fostering a disciplined study environment. The study concludes that educated women are pivotal in promoting family welfare, enhancing literacy rates, and driving social and economic progress within the community. It recommends strengthening educational opportunities for women to further amplify these positive impacts on family and community development.